Contribution of Lung Macrophages to the Inflammatory Responses Induced by Exposure to Air Pollutants - Kunihiko Hiraiwa; Stephan F. van Eeden (Mediators of Inflammation)
Large population cohort studies have indicated an association between exposure to particulate matter and cardiopulmonary morbidity and mortality. The inhalation of toxic environmental particles and gases impacts the innate and adaptive defense systems of the lung. Lung macrophages play a critically important role in the recognition and processing of any inhaled foreign material such as pathogens or particulate matter. Alveolar macrophages and lung epithelial cells are the predominant cells that process and remove inhaled particulate matter from the lung. Cooperatively, they produce proinflammatory mediators when exposed to atmospheric particles. These mediators produce integrated local (lung, controlled predominantly by epithelial cells) and systemic (bone marrow and vascular system, controlled predominantly by macrophages) inflammatory responses. The systemic response results in an increase in the release of leukocytes from the bone marrow and an increased production of acute phase proteins from the liver, with both factors impacting blood vessels and leading to destabilization of existing atherosclerotic plaques. This review focuses on lung macrophages and their role in orchestrating the inflammatory responses induced by exposure to air pollutants.